2023
DOI: 10.1002/cjoc.202200837
|View full text |Cite
|
Sign up to set email alerts
|

Sm and S Co‐doping to Construct Homo‐hetero Cu Catalysts for Synergistic Enhancing CO2 Electroreduction

Abstract: Copper (Cu) is recognized as one of the most efficient metal catalysts that can perform the electrocatalytic CO 2 reduction reaction (CO 2 RR) and its surface oxidation state determines the reaction pathway. The Cu δ+ (0 < δ < 1) species, are well known active sites in CO 2 RR to produce hydrocarbons and oxygenates. However, Cu δ+ active sites are difficult to control, and it is very easy to be reduced to Cu 0 under CO 2 RR operating conditions. Herein, we report a homo-hetero doping strategy to construct an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…It is worth noting that Co 1 ‐SNC exhibits a much higher current density and smaller onset potential compared to Co 1 ‐NC in the CO 2 ‐saturated electrolyte, indicating a superior CO 2 RR performance. [ 31 ] Furthermore, according to Figures 3a and b, Co 1 −NSC exhibits a much higher FE CO and larger j CO than those of Co 1 −NC across all testing potentials. The maximum FE CO of Co 1 −SNC reaches 75.6% ± 2% at –0.8 V. Besides, no liquid products can be detected (Figure S5).…”
Section: Resultsmentioning
confidence: 91%
“…It is worth noting that Co 1 ‐SNC exhibits a much higher current density and smaller onset potential compared to Co 1 ‐NC in the CO 2 ‐saturated electrolyte, indicating a superior CO 2 RR performance. [ 31 ] Furthermore, according to Figures 3a and b, Co 1 −NSC exhibits a much higher FE CO and larger j CO than those of Co 1 −NC across all testing potentials. The maximum FE CO of Co 1 −SNC reaches 75.6% ± 2% at –0.8 V. Besides, no liquid products can be detected (Figure S5).…”
Section: Resultsmentioning
confidence: 91%
“…In the Cu LMM spectra (Figure 2B), the peak centered at 570.6 eV indicating the Cu + state was the main species on the surface of catalysts before and after reaction. [ 29‐31 ] As shown in Figure S4, the In 3d core level spectra of In 2 O 3 and Cu/In 2 O 3 appear at 444.1 and 451.7 eV. They are assigned to the In 3d 5/2 and In 3d 3/2 , respectively, suggesting that the indium valence exists mainly as +3 for the three samples.…”
Section: Resultsmentioning
confidence: 93%
“…During the development of catalysts, researchers have found that altering the coordination microenvironment of metal center may impact on the activity of the active sites, which can affect the energy barrier of CO 2 activation and open up new prospects for designing CO 2 reduction catalysts. [ 20‐24 ] By changing the coordination microenvironment of Cu center from Cu 1 P 3 to Cu 1 N 3 , Li group tuned the Cu 3d electron energy in phosphorus carbon nitride (PCN) supported single‐Cu‐atom catalyst. The Cu 1 N 3 @PCN with the d ‐band center near the Fermi level showed enhanced catalytic activity for CO 2 photoreduction to CO, with a rate of 49.8 μmol·g cat –1 ·h –1 .…”
Section: Background and Originality Contentmentioning
confidence: 99%